A Vertiginous Experience: Historical Ethics and Practice in the Age of Trump. Issue 3 (August 2021) - Middleton, Simon
Abstract: This essay considers Christopher Tomlins' thoughts—as expressed in his In the Matter of Nat Turner: A Speculative History —on historical ethics and practice in the context of recent and ongoing controversies concerning the history of race and slavery in the American past. Tomlins endeavors to recover as much as he can relating to Nat Turner and his mentalité at the time of the infamous 1831 rebellion. He also promises a self-conscious engagement with the creation of history as an intellectual practice, and invites readers to reflect on their standpoint in the histories they create. For Tomlins this practice means a close reading of Turner's "confession" through the work of social theorists, an approach that will likely prove controversial for some readers. For those who stay with him, however, Tomlins provides a bravura demonstration of historical methodology with implications for current debates and divisions within the wider field.